Aktivitas Peran Mahasiswa dalam Meningkatkan Pendidikan di Nagori Purbasari - Purba, Zainal Arifin; Walid, Muhammad; Ningsih, Devi Fitriya; Aprilla, Vanya (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
In an effort to make the nation's life more intelligent, one of the activities that KKN students need to carry out is activities in the field of education. KKN students are expected to be able to develop various community service activity programs, one of which also touches on educational aspects. One of the locations chosen was Purbasari Village, Tapian Dolok District, Simalungun Regency as a KKN location. Judging from the type of information, the research approach used in this research is a qualitative approach. This research shows that the KKN-32 group plays a good and influential role for village communities and for educational institutions in the village in improving children's education in the village and empowering the community. In this case, the KKN-32 group in Purbasari Village, Tapian Dolok District, Simalungun Regency has a good role in helping the community and village educational institutions in improving education.